Self assessment and review ENT - Hans, Sakshi Arora (Jaypee Brothers Medical Publishers (P) Ltd, 2015)
This is a self-assessment based text comprised of 125 questions based on colour photographs or appropriate radiographs or scans. The questions involve a mixture of styles, some question "what will this show?" while others show a disease and ask about the presenting signs and symptoms